Slope Stability Analysis Using Electrical Resistivity Tomography and Limit Equilibrium Method: A Case Study from Girimulyo, Kulon Progo - Santie, Putri Anjary Widya; Wilopo, Wahyu; Faris, Fikri (Geological Engineering Department Universitas Gadjah Mada, 2024)
Girimulyo sub-district is one of the areas with high landslide risk in Kulon Progo Regency. On March 12, 2018, a landslide occurred in the area. Seven families were affected, and landslide material blocked the road. This study aims to determine slope conditions through electrical resistivity tomography (ERT) and slope stability analysis using the limit equilibrium method. Based on the interpretation of the ERT profile, it is known that a layer with a resistivity value of <5 Ωm is wet clay; 5-15 Ωm is wet silt; 15-150 Ωm is silt-to-sand; and >150 Ωm is bedrock. The sliding surface is thought to be at the boundary between the wet clay and wet silt layers. The interpretation of the ERT profile is confirmed by data from laboratory tests on soil samples. Slope stability analysis was carried out using ERT profile interpretation and soil sample laboratory test data. The slope stability analysis results show that both the slopes that experienced landslides in 2018 and those that did not experience landslides were stable when the water table was 3 meters deep. However, the landslide slopes are in critical condition as the groundwater level rises, while the non-landslide slopes are remains stable.